Genesis, Pathways, and Terminations of Intense Global Water Vapor Transport in Association with Large‐Scale Climate Patterns. Issue 24 (26th December 2017) - Sellars, S. L.; Kawzenuk, B.; Nguyen, P.; Ralph, F. M.; Sorooshian, S.
Abstract: The CONNected objECT (CONNECT) algorithm is applied to global Integrated Water Vapor Transport data from the NASA's Modern‐Era Retrospective Analysis for Research and Applications – Version 2 reanalysis product for the period of 1980 to 2016. The algorithm generates life‐cycle records in time and space evolving strong vapor transport events. We show five regions, located in the midlatitudes, where events typically exist (off the coast of the southeast United States, eastern China, eastern South America, off the southern tip of South Africa, and in the southeastern Pacific Ocean). Global statistics show distinct genesis and termination regions and global seasonal peak frequency during Northern Hemisphere late fall/winter and Southern Hemisphere winter. In addition, the event frequency and geographical location are shown to be modulated by the Arctic Oscillation, Pacific North American Pattern, and the quasi‐biennial oscillation. Moreover, a positive linear trend in the annual number of objects is reported, increasing by 3.58 objects year‐over‐year. Key Points: Tracking the life cycle of Integrated Water Vapor Transport (IVT) as "objects" provides unique empirical and descriptive data IVT objects typically exist five distinct regions, and their frequency of occurrence is strongly modulated by the AO, QBO, and PNA Results indicate that intense IVT objects are increasing globally by 3.58 events per year (95% confidence interval of ±1.39) Plain Language Summary: A computational science approach to tracking global atmospheric water vapor plumes is applied to a NASA data set from 1980 to 2016. Results show regions of the globe where intense water vapor transport often exists, including their genesis and termination locations. Winter time months tend to have more water vapor plumes in both the Southern and Northern Hemispheres. In addition, climate phenomena also have an impact on the frequency and location of these water vapor plumes.